Вимога щодо юридичної освіти та стажу професійної діяльності як структурний елемент конституційно-правового статусу суддів в Україні - Кравчук, В.; Kravchuk, V. (Східноєвропейський національний університет імені Лесі Українки, 2019)
Статтю присвячено аналізу вітчизняного та зарубіжного конституційного законодавства про судоустрій і статус суддів в частині вимоги щодо юридичної освіти та стажу професійної діяльності. Вимога щодо юридичної освіти та стажу професійної діяльності зумовлені публічно-правовим характером суддівської діяльності. Вимога щодо юридичної освіти та стажу професійної діяльності розглядається як один з елементів конституційно-правового статусу суддів. Проведений аналіз свідчить, що чинна редакція ч. 3 ст. 127 Конституції України враховує позитивний зарубіжний досвід та в цілому, відповідає європейським демократичним стандартам, а конституційні положення конкретизуються у відповідному спеціальному законі.The article is devoted to the analysis of the Ukrainian and foreign constitutional legislation on the judicial system and the status of judges in terms of the requirements for legal education and professional experience. The key findings of the research argue that the study of the nature of the constitutional and legal status of judge institute is not possible without characterization of its constituent elements. Until recently, the requirements for legal education and professional experience in the constitutional law science lack theoretical grounding. The analysis shows that the current wording of Part 3 of Article 127 of the Constitution of Ukraine takes into account the positive foreign experience and, in general meets the European democratic standards, and the constitutional provisions are specified in the relevant special law. The requirement for legal education and professional experience is an additional (non-core) element of the judge’s legal status as it affects the scope of his rights and responsibilities. In addition, the requirement for legal education and professional experience of candidates for judicial office is conditioned by the need to guarantee for the individuals and legal entities impartial, objective and timely justice, provided by qualified judges with the proper level of professional training.
The Requirement for Legal Education and Professional Experience as a Structural Component of the Constitutional and Legal Status of Judges in Ukraine
Keywords: конституційно-правовий статус суддів; правовий статус суддів; стаж професійної діяльності; суддя; юридична освіта; constitutional and legal status of judges; legal status of judges; professional experience as required by legal education and professional experience; judge; legal education